TINJAUAN ATAS PELAKSANAAN PEMOTONGAN, PELAPORAN DAN PENCATATAN AKUNTANSI PAJAK TERHADAP PPH PASAL 21 ATAS GAJI PEGAWAI TETAP PADA PT BAURE PRATAMA INDONESIA PERIODE DESEMBER 2014 - ITA BATUBARA; Desideria Regina; Frangky Yosua Sitorus (Buletin Ekonomi, 2018)
The author chose PT Bauer Pratama Indonesia, which is a company engaged in construction and manufacturing. PT Bauer Pratama Indonesia is not only in Indonesia but has internasional.in some case there own policies set out in the tax system, therefore, the writer wanted to know whether in terms of the implementation of the obligations of Article 21 Income Tax on salaries of employees of the company, especially in cutting, deposit , reporting and recordkeeping in accordance with statutory provisions and regulations applicable tax.The conclusions that can be authors obtained as a result of street vendors and discussion as well as the research that has been conducted at PT Bauer Pratama Indonesia on review for withholding, depositing, reporting and accounting income tax on salaries of 21 employees remain, namely.Calculation and Reporting has been done properly in accordance with the laws OF no.36 of 2008 regarding Fourth Amendment to Law No. 7 of 1983 Tax cuts Penghasilan. And income tax on salaries of permanent employee who has PT Bauer Pratama Indonesia done in accordance with the PER-31 / PJ / 2012. Recording the accounting for income taxes in accordance with article 21 already existing financial accounting standards except for depositing schedule.Keywords: obligations, deposit, Law